2020
DOI: 10.1101/2020.05.14.096016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional profiling reveals potential involvement of microvillous TRPM5-expressing cells in viral infection of the olfactory epithelium

Abstract: BackgroundUnderstanding viral infection of the olfactory epithelium is essential because smell loss can occur with coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus clade 2 (SARS-CoV-2), and because the olfactory nerve is an important route of entry for viruses to the central nervous system. Specialized chemosensory epithelial cells that express the transient receptor potential cation channel subfamily M member 5 (TRPM5) are found throughout the airways and intestinal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 103 publications
1
19
1
2
Order By: Relevance
“…Bowman's glands, for example, secrete mucus, which is essential to normal odor detection (Dear et al, 1991;Kern, 2000;Solbu and Holen, 2012). Sustentacular and microvillar cells remain somewhat mysterious, but seem to structurally support sensory neurons, phagocytose and/or detoxify potentially damaging agents, generate inflammatory cytokines, manage energetics through delivery of glucose to OSNs, and maintain local salt and water balance (Baxter et al, 2020;Lemons et al, 2017;O'Leary et al, 2019;Suzuki et al, 1996;Ualiyeva et al, 2020;Vogalis et al, 2005). Damage to support cells thus has the potential to change ion gradients and fuel availability, which in turn could acutely influence OSN firing rates.…”
Section: Inferring Disease Mechanisms From Patterns Of Gene Expressionmentioning
confidence: 99%
“…Bowman's glands, for example, secrete mucus, which is essential to normal odor detection (Dear et al, 1991;Kern, 2000;Solbu and Holen, 2012). Sustentacular and microvillar cells remain somewhat mysterious, but seem to structurally support sensory neurons, phagocytose and/or detoxify potentially damaging agents, generate inflammatory cytokines, manage energetics through delivery of glucose to OSNs, and maintain local salt and water balance (Baxter et al, 2020;Lemons et al, 2017;O'Leary et al, 2019;Suzuki et al, 1996;Ualiyeva et al, 2020;Vogalis et al, 2005). Damage to support cells thus has the potential to change ion gradients and fuel availability, which in turn could acutely influence OSN firing rates.…”
Section: Inferring Disease Mechanisms From Patterns Of Gene Expressionmentioning
confidence: 99%
“…They were also the first to localize the virus entry proteins to distinct cell types in the olfactory epithelium ( Bilinska et al 2020 ; Table 2 ). There is now an emerging consensus that mature olfactory neurons do not express the virus entry proteins, ACE2 and TMPRSS2, at least not at significant levels, and not in the large majority of the mature olfactory neurons in mouse and human ( Baxter and others 2020 ; Bilinska and others 2020 ; Brann and others 2020 ; Chen and others 2020b ; Fodoulian and others 2020 ; Gupta and others 2020 ; Klingenstein and others 2020 ; Ziegler and others 2020 —see Table 2 ). A recent study that localized the SARS-CoV-2 virus in the hamster olfactory epithelium confirmed this notion by showing that sustentacular cells contained the virus, but not olfactory neurons ( Bryche and others 2020 ).…”
Section: Anosmia In Covid-19: What Is the Underlying Mechanism?mentioning
confidence: 99%
“…It is now well established that most of the olfactory receptor neurons do not express the virus entry proteins, ACE2 and TMPRSS2 ( Baxter and others 2020 ; Bilinska and others 2020 ; Brann and others 2020 ; Chen and others 2020b ; Fodoulian and others 2020 ; Gupta and others 2020 ; Klingenstein and others 2020 ; Table 2 ), and consistent with the absence of the entry proteins, there is no convincing evidence that olfactory receptor neurons accumulate SARS-CoV-2, neither in animal models ( Bryche and others 2020 ; Sia and others 2020 ) nor in humans ( Meinhardt and others 2020 ). But just because the olfactory receptor neurons do not express the two entry proteins for the virus, or only at very low levels (TMPRSS2), is it safe to assume that SARS-CoV viruses cannot utilize the olfactory route to the brain?…”
Section: Is There a Route For Sars-cov-2 From The Nose To The Brain?mentioning
confidence: 99%
“… 5 Deep transcriptional profiling of flow-cytometry-sorted OE cell types suggests that microvillous cells (MVCs) and a small subset of TRPM5-expressing ORNs are likely involved in the inflammatory response to viral infection. 8 …”
Section: Inflammatory Processes—other Side Of the Same Coin?mentioning
confidence: 99%